2022
DOI: 10.1002/ange.202204383
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbranched Polyborate: A Non‐conjugated Fluorescent Polymer with Unanticipated High Quantum Yield and Multicolor Emission

Abstract: Non‐conjugated fluorescent polymers have attracted great attention due to their excellent biocompatibility and environmental friendliness. However, it remains a huge challenge to obtain a polymer with high fluorescence quantum yield (QY) and multicolor emission simultaneously. Herein, we reported three kinds of nonaromatic hyperbranched polyborates (P1–P3) with multicolor emission, surprisingly, P2 also exhibits an unanticipated high QY (54.1 %). The natural bond orbital (NBO) analysis and density functional t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 61 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…8e and 8f. The resonance peaks of acetylene carbon of TMP at 74.0 and 75.8 ppm disappeared in the 13 C CP/MAS NMR spectrum of PTMP. Instead, two new resonance peaks of C=C (f, g) are observed.…”
Section: H 2 O-involved Interfacial Polymerizationmentioning
confidence: 97%
See 2 more Smart Citations
“…8e and 8f. The resonance peaks of acetylene carbon of TMP at 74.0 and 75.8 ppm disappeared in the 13 C CP/MAS NMR spectrum of PTMP. Instead, two new resonance peaks of C=C (f, g) are observed.…”
Section: H 2 O-involved Interfacial Polymerizationmentioning
confidence: 97%
“…Instead, two new stretching vibration peaks of C=C at 1617 cm −1 and C=C−O at 1116 cm −1 are observed. 52 The 13 C NMR spectrum of TMP and 13 C CP/MAS NMR spectrum of PTMP are also given in Figs. 8e and 8f.…”
Section: H 2 O-involved Interfacial Polymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…This is attributed to the formation of WPU−Fe 3+ complex, and the large charge radius ratio of Fe 3+ makes the intermolecular charge transfer of WPU to Fe 3+ occur. 25,36,37…”
Section: Series Of Applicationsmentioning
confidence: 99%
“…By employing polymerization, chemical crosslinking, or hydrothermal treatment methods, covalent bonds are formed among the polymer structures, which immobilize the sub-fluorophore groups, rigidify the structures and thus enhance the photoluminescence of these materials. 8 Previously, Tang et al synthesized non-conjugated hyperbranched polyborates, 13 which exhibited an unanticipated high quantum yield of 54.1%. In a pioneering study by Yang and co-workers, they reported various fluorescent non-conjugated polymer dots (NCPDs) prepared by the hydrothermal treatment.…”
Section: Introductionmentioning
confidence: 99%